2018
DOI: 10.4236/jct.2018.91007
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Examination and Ultrasonography as Predictors of Lateral Neck Lymph Nodes Metastasis in Primary Well Differentiated Thyroid Cancer

Abstract: Background: Lateral neck dissection is risky and should be performed only as a therapeutic intervention for known disease. Aim of the Study: This study aims at finding predictors which help in selecting patients who have high risk of lymph node metastasis. Methods: All the patients with well differentiated thyroid cancer underwent thyroidectomy with lateral lymph nodes (LNs) dissection with available pathology report and sufficient data have been included in the study. Results: Sixty nine patients have been in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…Amin et al . suggested that clinical examinations and ultrasonography examinations are the most independent and reliable factors to detect lateral neck lymph nodes involvement 28 . Ultrasonography, enhanced CT, and MRI might have some significance in evaluating neck lymph nodes in the treatment of thyroid carcinoma.…”
Section: Discussionmentioning
confidence: 99%
“…Amin et al . suggested that clinical examinations and ultrasonography examinations are the most independent and reliable factors to detect lateral neck lymph nodes involvement 28 . Ultrasonography, enhanced CT, and MRI might have some significance in evaluating neck lymph nodes in the treatment of thyroid carcinoma.…”
Section: Discussionmentioning
confidence: 99%